Techno Phobia and Academic Excellence among Higher Secondary School Students in the Nilgiris District - Karuppusamy, A.; Senthilkumaran, M. (Journal of Ecohumanism, 2024)
This article focuses on the technophobia and academic excellence for the higher secondary school students in The Nilgiris district, Tamilnadu, India. The main objective of the study to find out the level of technophobia and academic excellence of higher secondary school students in The Nilgiris district based on some demographic variables (such as gender, medium of Instruction, Locality). The data were collected for the survey method at eleventh twelfth standard school students in The Nilgiris district. The researcher were used a standardised tool. The descriptive analysis and Karl Pearson correlation was used in this study. The major findings are high level of significance difference between technophobia of higher secondary school students in The Nilgiris district. The average level of significance difference between academic excellences of higher secondary school students in The Nilgiris district. There is a high positive correlation for technophobia and academic excellence of higher secondary school students in The Nilgiris district.